Exploring New CGRP Family Peptides and their Receptors in Vertebrates - Takei, Yoshio; Ogoshi, Maho; Nobata, Shigenori (Current Protein and Peptide Science, 2013)
Vertebrates have expanded their habitats from aquatic to terrestrial environments, which has accompanied the evolution of cardiovascular and osmoregulatory hormones. Specifically, mammals have developed mechanisms to maintain high blood pressure and blood volume, while extant fishes have developed hypotensive and Na-extruding mechanisms to adapt to the marine environment where they underwent a vast diversification. The CGRP family is one of the hormone systems that decrease blood pressure and blood volume. Within the CGRP family of teleost fishes, we found that adrenomedullins (AMs) have diversified and five paralogs (AM1-5) form an independent subfamily. Based on this discovery in fishes, we found AM2 and AM5 in mammals. In mammalian species that have AM2 and/or AM5, the peptides assume greater importance in the case of pathophysiological disturbances in pressure and fluid balance such as hypertension and cardiac and renal failure. In addition, novel functions of AM peptides have been suggested by the discovery of AM2 and AM5 in mammals. Current research on the CGRP family is focused on the identification of new receptors for AM2/AM5 and the establishment of AM2 knockout mice, which will enable new developments in the basic and clinical research on this intriguing hormone family. Importantly, comparative fish studies can contribute to new developments in our understanding of the function of the AM peptides.
Keywords: functional evolution